A powerful resource to improve school coexistence: Mediation (Journal of Parents and Teachers, 2014)
From confrontation to cooperation there is a long way. Mediation, thanks to its impartiality, is a good strategy to get through this way successfully. However, mediation has its limits, so it must go with some other resources oriented to conflict management. The steps to follow a good mediation are: presentation and game rules, clarifying the problem, explaining the problem, suggesting solutions and getting to an agreement.
Keywords: orientation and values; experiences; school coexistence; mediation; tutorial action.